Post-operative gamma knife radiosurgery for WHO grade I intracranial meningiomas: A single-center, retrospective study - Yu, Jinxiu; Zeng, Jiamin; Hu, Guanye; Wang, Jing; Chen, Guohao; Huang, Minyi; Liang, Shunyao; He, Yong; Deng, Yinhui; Gong, Ye; Fu, Junyi (Frontiers in Neurology, 2023)
Objective To explore the results of the Gamma Knife radiosurgery (GKRS) for World Health Organization (WHO) grade I intracranial meningiomas after surgical resection. Methods A total of 130 patients who were pathologically diagnosed as having WHO grade I meningiomas and who underwent post-operative GKRS were retrospectively reviewed in a single center. Results Of the 130 patients, 51 patients (39.2%) presented with radiological tumor progression with a median follow-up time of 79.7 months (ranging from 24.0 to 291.3 months). The median time to radiological tumor progression was 73.4 months (ranging from 21.4 to 285.3 months), whereas 1-, 3-, 5-, and 10-year radiological progression-free survival (PFS) was 100, 90, 78, and 47%, respectively. Moreover, 36 patients (27.7%) presented with clinical tumor progression. Clinical PFS at 1, 3, 5, and 10 years was 96, 91, 84, and 67%, respectively. After GKRS, 25 patients (19.2%) developed adverse effects, including radiation-induced edema (n = 22). In a multivariate analysis, a tumor volume of ≥10 ml and falx/parasagittal/convexity/intraventricular location were significantly associated with radiological PFS [hazard ratio (HR) = 1.841, 95% confidence interval (CI) = 1.018–3.331, p = 0.044; HR = 1.761, 95% CI = 1.008–3.077, p = 0.047]. In a multivariate analysis, a tumor volume of ≥10 ml was associated with radiation-induced edema (HR = 2.418, 95% CI = 1.014–5.771, p = 0.047). Of patients who presented with radiological tumor progression, nine were diagnosed with malignant transformation. The median time to malignant transformation was 111.7 months (ranging from 35.0 to 177.2 months). Clinical PFS after repeat GKRS was 49 and 20% at 3 and 5 years, respectively. Secondary WHO grade II meningiomas were significantly associated with a shorter PFS (p = 0.026). Conclusions Post-operative GKRS is a safe and effective treatment for WHO grade I intracranial meningiomas. Large tumor volume and falx/parasagittal/convexity/intraventricular location were associated with radiological tumor progression. Malignant transformation was one of the main cause of tumor progression in WHO grade I meningiomas after GKRS.